Association of genetic variants with skin pigmentation phenotype among populations of west Maharashtra, India. Issue 5 (26th February 2016) - Jonnalagadda, Manjari; Norton, Heather; Ozarkar, Shantanu; Kulkarni, Shaunak; Ashma, Richa
Abstract : Objectives: South Asians exhibit extensive variation in skin melanin index (MI) which is observed across the broader region of South Asia as well as within restricted geographic regions. However, the genetic variants associated with variation in the skin pigmentation phenotype are poorly understood in these populations. The present study examines the association between MI measures and genetic variants from 5 candidate pigmentation genes among 533 individuals representing 6 populations of West Maharashtra. Methods: Associations between five single nucleotide polymorphisms (SNPs) known to play a role in pigmentation (rs1426654‐ SLC24A5, rs1042602‐ TYR, rs16891982‐ SLC45A2, rs6058017‐ ASIP, and rs642742‐ KITLG ) and MI measures were tested using standard one‐way analysis of variance (ANOVA) within each population. Multiple linear regression was used to test the effects of these SNPs in the full West Maharashtra sample using sex, age, and population or social group as covariates. Results: rs1426654 showed significant association with MI in all six study populations ( P  < 0.01). Association tests using sex, age, and population as covariates showed rs1426654 and rs1042602 to be significantly ( P  < 0.01) associated with lighter skin pigmentation in West Maharashtra as a whole. By contrast, when social group was added as a covariate instead of population, rs1426654, rs1042602, and rs16891982 were significantly ( P  < 0.01) associated with lighter skin pigmentation. Conclusions: Only rs1426654 is significantly associated with MI in each individual population; however, rs1426654, rs1042602, and rs16891982 are significantly associated with pigmentation in the broader West Maharashtra region after controlling for population and social group, with rs1426654 ( SLC24A5 ) explaining the majority of the observed variation. Am. J. Hum. Biol. 28:610–618, 2016. © 2016 Wiley Periodicals, Inc.